Continuum beliefs and attitudes towards people with mental illness: Results from a national survey in France. (May 2015) - Angermeyer, Matthias C; Millier, Aurélie; Rémuzat, Cécile; Refaï, Tarek; Schomerus, Georg; Toumi, Mondher
Background: Whether mental disorders should be considered as categorical or dimensional has found increasing attention among mental health professionals. Only little is known about what the public thinks about this issue. Aims: First, to assess how prevalent the belief in a continuum of symptoms from mental health to mental illness is among the general public. Second, to examine how continuum beliefs are associated with attitudes towards people with mental disorder. Methods: In 2012, an on-line survey was conducted in France ( N  = 1, 600). After the presentation of a case-vignette depicting a person with either schizophrenia or depression, belief in a continuum of symptoms, emotional reactions and desire for social distance related to the person in the vignette were assessed. Results: While 58.2% of respondents agreed in a symptom continuum for depression, this percentage was only 28.5% for schizophrenia. In both disorders, continuum beliefs were associated with more pro-social reactions and less desire for social distance. Only in schizophrenia, there was an inverse relationship with the expression of anger. Conclusions: There is increasing evidence of an association between continuum beliefs and positive attitudes towards people with mental illness. Information on the continuous nature of psychopathological phenomena may usefully be included in anti-stigma messages.